Otimização e validação de um método para o estudo da contaminação de BTEX em água, na cidade de Maringá, empregando extração por headspace e Cromatografia em fase gasosa acoplada à Espectrometria de Massas - Batista, Aline Fontana (2013)
The aromatic compounds benzene, toluene, ethylbenzene and the isomeric xylene (BTEX) are among the major contaminants from groundwater due to leakages from underground storage tanks of fuel. These compounds released into the environment cause harm to human health. The present work was carried out to optimize, validate and implement a method of extraction "headspace" and gas chromatography coupled to mass spectrometry (HS-GC-MS) for the separation and determination of BTEX in water. The extraction parameters were evaluated by a fractional factorial design 24-1, where it was investigated the influence of temperature and extraction time, the volume of the liquid and the addition of potassium chloride (KCl) in the extraction of analytes. The extraction temperature and volume of the liquid were the factors that most influenced the response. The best conditions for extraction were: 80 °C, 30 min, 15.0 mL and 2.00 g of KCl. The method was validated in terms of linearity, limit of detection and quantification, precision and accuracy. The calibration curves showed good linearity with values r2>0.999. The detection limits were found to 0.0295, 0.0160, 0.0124, 0.0273 and 0.0142 μg L-1 for benzene, toluene, ethylbenzene, m, p-xylene and o-xylene, respectively. The method showed good precision where the relative standard deviations obtained for concentrations of 0.05 and 0.10 μg L-1 were less than 7.35 %, and concentration of 5.00 μg L-1 of less than 1.98 %. Accuracy was evaluated by recovery, in two concentration levels (0.10 and 5.00 μg L-1) which showed recoveries between 102 and 112 %. The method was applied in water samples from artesian wells near gas stations of fuel, in the city of Maringá-PR. Toluene was the analyte found in the largest number of samples analyzed (62.5 %), with concentrations ranging from 0.14 to 8.01 μg L-1. The levels of BTEX found in all samples were below the contamination limits imposed by national legislation.